Iron uptake pathway of Escherichia coli as an entry route for peptide nucleic acids conjugated with a siderophore mimic - Tsylents, Uladzislava; Burmistrz, Michał; Wojciechowska, Monika; Stępień, Jan; Maj, Piotr; Trylska, Joanna (Frontiers in Microbiology, 2024)
Bacteria secrete various iron-chelators (siderophores), which scavenge Fe3+ from the environment, bind it with high affinity, and retrieve it inside the cell. After the Fe3+ uptake, bacteria extract the soluble iron(II) from the siderophore. Ferric siderophores are transported inside the cell via the TonB- and energy- dependent receptor-based system. Importantly, siderophore uptake paths have been also used by sideromycins, natural antibiotics. Our goal is to hijack the transport system for hydroxamate-type siderophores to deliver peptide nucleic acid oligomers into Escherichia coli cells. As siderophore mimics we designed and synthesized linear and cyclic Nδ-acetyl-Nδ-hydroxy-L-ornithine based peptides. Using circular dichroism spectroscopy, we found that iron(III) is coordinated by the linear trimer with hydroxamate groups but not by the cyclic peptide. The internal flexibility of the linear siderophore oxygen atoms and their interactions with Fe3+ were confirmed by all-atom molecular dynamics simulations. Using flow cytometry we found that the designed hydroxamate trimer transports PNA oligomers inside the E. coli cells. Growth recovery assays on various E. coli mutants suggest the pathway of this transport through the FhuE outer- membrane receptor, which is responsible for the uptake of the natural iron chelator, ferric-coprogen. This pathway also involves the FhuD periplasmic binding protein. Docking of the siderophores to the FhuE and FhuD receptor structures showed that binding of the hydroxamate trimer is energetically favorable corroborating the experimentally suggested uptake path. Therefore, this siderophore mimic, as well as its conjugate with PNA, is most probably internalized through the hydroxamate pathway.